Embolization of Renal Pseudoaneurysm Following Partial Nephrectomy of Localized Tumour and Preserving Renal Function: Clinical Case and Review of Literature - Ledas, Giedrius; Makevičius, Jurijus; Kurminas, Marius; Želvys, Arūnas; Miglinas, Marius; Jankevičius, Feliksas (Lietuvos chirurgija, 2022)
Surgical procedures in highly vascularized renal parenchyma sometimes can cause iatrogenic vascular complications. Although incidence renal pseudoaneurysms after partial nephrectomy is low, around 1%, clinical presentation of these patients can be quite severe – hematuria, lumbar pain, dizziness, weakness. Prompt and precise diagnostics and treatment are essential. Ultrasound and Computed Tomography are two most common diagnostic approaches for the assessment of pseudoaneurysms or arteriovenous fistulas following partial nephrectomy. Endovascular selective microcoil embolization is a safe and effective kidney-preserving procedure for treating iatrogenic vascular complications. Although when embolizing renal arteries some of renal parenchyma loses perfusion and becomes fibrotic, no significant decrease in renal function in early post-embolization period was noted. Comparing open surgery to endovascular treatment of pseudoaneurysms, latter one allows shorter average hospital stay and less frequent cardiac and peripheral vascular complications. The article discusses a case of a patient that had developed renal pseudoaneurysm after partial nephrectomy. During a routine check-up of a middle-aged woman a presumable renal cyst was found. On more throughout examination the cyst was ruled as a tumour and partial nephrectomy was performed. After 12 days from surgery patient was admitted to hospital complaining macrohematuria, lower abdomen pain, episodic right-side ache. Urgent contrast enhanced computed tomography was performed, which confirmed that patient was bleeding from the operated kidney. Patient was admitted to interventional radiology departament and perform embolization of bleeding vessel. After embolization of pseudoaneurysm, bleeding was controlled and patient was completely treated.
Keywords: pseudoaneurysm; kidney; treatment; embolization; partial nephrectomy